2017
DOI: 10.1111/bpa.12505
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping but distinct TDP‐43 and tau pathologic patterns in aged hippocampi

Abstract: Intracellular proteinaceous aggregates (inclusion bodies) are almost always detectable at autopsy in brains of elderly individuals. Inclusion bodies composed of TDP-43 and tau proteins often coexist in the same brain, and each of these pathologic biomarkers is associated independently with cognitive impairment. However, uncertainties remain about how the presence and neuroanatomical distribution of inclusion bodies correlate with underlying diseases including Alzheimer's disease (AD). To address this knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 85 publications
4
56
0
Order By: Relevance
“…Arnold et al reported that 40% of elderly individuals with TDP‐43 pathology had argyrophilic grains (AG) pathology, while the prevalence of AG in elderly individuals without TDP‐43 pathology was limited to less than 20% . However, another study indicated no interaction between AG‐tau and TDP‐43 pathologies in elderly individuals …”
Section: Tdp‐43 Pathology In Progressive Supranuclear Palsy Corticobsupporting
confidence: 71%
See 1 more Smart Citation
“…Arnold et al reported that 40% of elderly individuals with TDP‐43 pathology had argyrophilic grains (AG) pathology, while the prevalence of AG in elderly individuals without TDP‐43 pathology was limited to less than 20% . However, another study indicated no interaction between AG‐tau and TDP‐43 pathologies in elderly individuals …”
Section: Tdp‐43 Pathology In Progressive Supranuclear Palsy Corticobsupporting
confidence: 71%
“…50 However, another study indicated no interaction between AG-tau and TDP-43 pathologies in elderly individuals. 51…”
Section: Tdp-43 Pathology In Progressive Supranuclear Palsy Corticobmentioning
confidence: 99%
“…TDP‐43 pathology has also been reported in HS cases, and HS‐aging is strongly associated with TDP‐43 pathology . Nelson et al recommend “cerebral age‐related TDP‐43 and sclerosis” (CARTS), as a more appropriate term for TDP‐43 pathology and HS‐recognized, but AD pathology‐negative, cases . They also emphasized that the dentate fascia granule‐cell NFTs could provide a proxy indicator of CARTS pathology in cases lacking substantial AD pathology .…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Nelson et al recommend "cerebral age-related TDP-43 and sclerosis" (CARTS), as a more appropriate term for TDP-43 pathology and HS-recognized, but AD pathology-negative, cases. 15,18,19 They also emphasized that the dentate fascia granule-cell NFTs could provide a proxy indicator of CARTS pathology in cases lacking substantial AD pathology. 18 In contrast, if HS is observed in AD brains, comorbid TDP-43 pathology should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation